CHARACTERISTICS AND PERFORMANCE OF MEDICAL RECORDING OFFICERS IN THE FILING SECTION OF A REGIONAL GENERAL HOSPITAL OF NUSA TENGGARA BARAT PROVINCE - Yanti, Ni Komang Wijiani; Yulianti, Mega Sara (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Patient waiting time is a tangible manifestation of the performance of human resources. Based on the results of a preliminary study conducted by researchers on November 5, 2021 at the NTB Provincial Hospital, the problems that exist in the filing are delays in returning medical record files from inpatient care, incorrect file storage, wide medical record filing space, so the waiting time for the provision of medical record files not up to standard. The purpose of the study was to identify the characteristics and performance of medical record officers in the filing section of the NTB Provincial Hospital. This type of research is descriptive with a cross sectional design. The population of all medical record officers is 45 people with a sample of 25 people. The sampling technique used incidental sampling, data collection using a questionnaire. Data processing uses editing, coding, data entry, cleaning and data analysis using quantitative analysis with descriptive statistics, frequency distribution of characteristic variables and performance of medical record officers. The results of the research on the characteristics of medical record officers at the NTB Provincial Hospital showed that the average age was >30 years 60%, female sex 52%, diploma education 60%, training 96%, knowledge 88%, years of service >1 year 96%, and the performance level of medical record officers at the NTB Provincial Hospital in the sufficient category is 64%. The suggestion is that medical record officers need to increase knowledge through education as a medical recorder, the higher the education, the better the performance in carrying out the main tasks and functions included in the administration of medical record services at the NTB Provincial Hospital.